Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Edwards, Jena E.; Hiltz, Elizabeth; Broell, Franziska; Bushnell, Peter G.; Campana, Steven E.; Christiansen, Jørgen S.; Devine, Brynn M.; Gallant, Jeffrey J.; Hedges, Kevin J.; MacNeil, M. Aaron; McMeans, Bailey C.; Nielsen, Julius; et al. (Frontiers in Marine Science, 2019)
Long-lived species share life history traits such as slow growth, late maturity, and low fecundity, which lead to slow recovery rates and increase a population’s vulnerability to disturbance. The Greenland shark (Somniosus microcephalus) has recently been recognized as the world’s longest-lived vertebrate, but many questions regarding its biology, physiology, and ecology remain unanswered. Here we review how current and future research will fill knowledge gaps about the Greenland shark and provide an overall framework to guide research and management priorities for this species. Key advances include the potential for specialised ageing techniques and demographic studies to shed light on the distribution and age-class structure of Greenland shark populations. Advances in population genetics and genomics will reveal key factors contributing to the Greenland shark’s extreme longevity, range and population size, and susceptibility to environmental change. New tagging technologies and improvements in experimental and analytical design will allow detailed monitoring of movement behaviours and interactions among Greenland sharks and other marine species, while shedding light on habitat use and susceptibility to fisheries interactions. Interdisciplinary approaches, such as the combined use of stable isotope analysis and high-tech data-logging devices (i.e. accelerometers and acoustic hydrophones) have the potential to improve knowledge of feeding strategies, predatory capabilities, and the trophic role of Greenland sharks. Measures of physiology, including estimation of metabolic rate, as well as heart rate and function, will advance our understanding of the causes and consequences of long lifespans. Determining the extent and effects of current threats (as well as potential mitigation measures) will assist the development of policies, recommendations, and actions relevant for the management of this potentially vulnerable species. Through an interdisciplinary lens, we propose innovative approaches to direct the future study of Greenland sharks and promote the consideration of longevity as an important factor in research on aquatic and terrestrial predators.